Children reading spoken words: Interactions between vocabulary and orthographic expectancy - Wegener, S; Wang, H; de Lissa, P; Robidoux, S; Nation, K; Castles, A (Wiley, 2017)
There is an established association between children’s oral vocabulary and their word reading but its basis is not well-understood. Here, we present evidence from eye movements for a novel mechanism underlying this association. Two groups of 18 Grade 4 children received oral vocabulary training on one set of 16 novel words (e.g. “nesh”, “coib”), but no training on another set. The words were assigned spellings that were either predictable from phonology (e.g., nesh) or unpredictable (e.g., koyb). These were subsequently shown in print, embedded in sentences. Reading times were shorter for orally familiar than unfamiliar items, and for words with predictable than unpredictable spellings but, importantly, there was an interaction between the two: children demonstrated a larger benefit of oral familiarity for predictable than for unpredictable items. These findings indicate that children form initial orthographic expectations about spoken words before first seeing them in print.